The Effect of Intercropping and leaf Fertilizer on the Growth and Production of Chili, Eggplant and Tomato Plants. - Nuril Huda; Al Machfudz WDP (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effect of intercropping and leaf fertilizer on the growth and production of chili, eggplant and tomato plants. This research was conducted in the village of Jiken, Tulangann Subdistrict, Sidoarjo Regency, starting in January 2019 until April 2019. The research was arranged factorial using a randomized block design followed by BNJ 5% was repeated 3 times with the first factor being intercropping con- sisting of intercropping of chili with tomatoes (T1) and intercropping chili with eggplant (T2). The second factor is without the use of leaf fertilizer (D0), using leaf fertilizer with complex micro content (D1) and using leaf fertilizer with macro and micro content (D2). Variables observed were plant height, stem diameter, number of leaves, weight of fruit. The results showed that there was no interaction between intercropping and leaf fertilizer on the growth and production of chili, the intercropping treatment had a significant effect on the growth and yield of chili production, while in the treatment of leaf fertilizer there was a significant effect on the number of chili leaves at 35 HST.